Structural and photocatalytic dye degradation properties of Li2Mn0.95Ru0.05O3. (2021) - Singh, Priyanka; Singh, Brajendra
Abstract: In the present study, we have documented the structural and dye degradation properties of Li2 Mn0.95 Ru0.05 O3 synthesized using solid state synthesis method. X-ray diffraction studies show the single phase composition with Ru doping at Mn site in Li2 MnO3 and change in lattice parameters. Raman peaks show the shift in Mn-O stretching mode for Li2 MnO3 towards lower wave number and Ag stretching mode of Mn – O vibrations show multiple peaks in Li2 Mn0.95 Ru0.05 O3 . Soft X-ray absorption spectroscopic studies show the presence of mixed valences of Ru +4 /Ru +5 in Li2 Mn0.95 Ru0.05 O3 . The amount 5 mg of Li2 Mn0.95 Ru0.05 O3 degrades 5 ml of (10 mg/L) concentrated methylene blue solution in ∼ 8 min of exposure in visible light. In these studies, we have explored new reusable catalyst which uses redox interaction of Ru-Mn to degrade methylene blue dye solutions.